FINANCIAL FEASIBILITY ANALYSIS OF SWAMP BUFFALO FARMING IN NORTH KONAWE REGENCY - La Ode Arsad Sani; Muh Haidir Hakim (AgriMu, 2026)
This study aims to analyze the financial feasibility of swamp buffalo farming in North Konawe Regency, particularly in Wiwirano and Landawe Districts. The study was conducted from September to November 2025 using a descriptive quantitative approach through a survey method involving 30 farmers selected purposively. Primary data were collected through structured interviews using questionnaires, while secondary data were obtained from Statistics Indonesia (BPS) and relevant literature. The analysis covered revenue, production costs, income, Net Present Value (NPV), Net Benefit-Cost Ratio (NBCR), Payback Period (PBP), and sensitivity analysis. The results showed that most farmers were of productive age, with an average livestock ownership scale of 1–5 animals. Business income increased from a loss of IDR 146,762,637 in 2020 to a profit of IDR 348,237,363 in 2024, along with the increase in revenue from livestock sales. The financial feasibility analysis indicated that the business was feasible to operate, with an NPV of IDR 258,228,973, an NBCR of 2.22, and a PBP of 3.35 years. Under a 15% change scenario, the business remained feasible despite a decline in feasibility indicators. Therefore, swamp buffalo farming in North Konawe has good economic prospects and has the potential to be developed sustainably through improved business management.